Image based face detection using probabilistic neural network - Hashim, Nik Mohd Zarifie; Wan Mazlan, Wan Nurul Alia; Aziz, Khairul Azha A (2014)
This paper presents an image based face detection using probabilistic neural network. The purpose is to localize and extract the face region from the background that will be fed into the face recognition system for identification. General preprocessing approach was used for normalizing the image and a Probabilistic Neural Network (PNN) was used to distinguish between face and non-face images. Probabilistic neural networks can be used for classification problems. The performance of the PNN face detection system will be based on the detection rate, False Acceptance Rate (FAR) and the False Rejection Rate (FRR) criteria.